Christmas city - Garland, Michael, 1952- (Dutton Children's Books, 2002)
"On Christmas Eve, Tommy receives an intriguing invitation from his eccentric Aunt Jeanne and is soon whisked away in a magical taxi to a bustling metropolis where it's Christmas every day"--Dust jacket.